THE GOBY FISH COLLECTION IN THE WATERSHED AREA OF TOLITOLI, CENTRAL SULAWESI, INDONESIA - Laheng, Suardi; Paisal, Moh.; Irmawati, Irmawati; Selvi, Selvi; Nurfauzan, Malik (Jurusan Perikanan dan Kelautan, 2025)
Central Sulawesi has a diverse diversity of ichthyofauna. Gobies are one type of fish abundant in fresh water and can be found from the upstream to the downstream of the river. The abundance and information on the types of gobies are still limited in several rivers in Central Sulawesi. Tolitoli Regency is one of the areas that still has minimal information on the diversity of gobies, so it is necessary to research collecting gobies in the watershed in Tolitoli Regency. The research was conducted from July 2020 to December 2020 in the watershed of Baolan District (Dadakitan Village, Buntuna Village, and Tambun Village), Tolitoli, Central Sulawesi. The sampling locations in the watershed are divided into 3 parts, namely the upstream, middle, and downstream. Gobies were collected using the pore sampling method by preparing eight observation stations. Specimens were collected using nets (size 20 x 20 cm) with the method of catching against the current. The caught fish were kept in a mini aquarium and then documented using a digital camera. Furthermore, the fish were preserved using 70% alcohol for identification. The results of the study showed that the collection of goby fish in the Tolitoli watershed, Central Sulawesi, was found to be 408 individuals consisting of 4 families (Butidae, Eleotridae, Gobiidae, Oxudercidae), 12 genera (Butis, Oxyeleotris, Belobranchus, Eleotris, Giuris, Redigobius, Awaous, Lentipes, Stiphodon, Sicyopus, Sicyopterus), and 16 species (Butis sp., Redigobius sp., Sicyopterus sp., Stiphodon semoni, Stiphodon sp., Awaous sp., Belobranchus sp., Schismatogobius sp.1, Schismatogobius sp.2, Eleotris fusca, Oxyeleotris sp., Giuris sp., Sicyopus zosterophorus, Sicyopus sp.1, Sicyopus sp.2, Lentipes sp.). The highest abundance of goby fish species in the Tolitoli Watershed is Stiphodon semoni (47,79%). Keywords: Amphidromus, sustainability, aquatic organisms.